# SOLUTION: Please help with the following: If g(x) = x ^2 - 3x, find what the square root of (g(-1) ) is. I started with: the square root of g times -1 = the square root of 1^2 - 3 t

Algebra ->  Algebra  -> Functions -> SOLUTION: Please help with the following: If g(x) = x ^2 - 3x, find what the square root of (g(-1) ) is. I started with: the square root of g times -1 = the square root of 1^2 - 3 t      Log On

 Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations! Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help!

 Algebra: Functions, Domain, NOT graphing Solvers Lessons Answers archive Quiz In Depth

 Question 16693: Please help with the following: If g(x) = x ^2 - 3x, find what the square root of (g(-1) ) is. I started with: the square root of g times -1 = the square root of 1^2 - 3 times the square root of -1 the square root of g times -1 = 1- 3, times the square root of -1 the square root of g times -1 = -2, times the square root of -1 the teacher's answer is 2 and I'm not sure how he got it and if it would be "the square root of g times -1" = 2. Please help!Answer by bam878s(77)   (Show Source): You can put this solution on YOUR website!First of all you're interpreting the problem wrong. g(-1) doesn't mean g * -1. g is a function so it depends on certain parameter x. We know g(x) = so to find g (-1) you simply put the value of x = -1 into the equation. = 1 + 3 = 4. Now you need to find } which is simply = 2. Hope this helps.